Flocculation of flotation tailings using thermosensitive polymers - Bogacz Wojciech; Lemanowicz Marcin; Gierczycki Andrzej; Mielańczyk Anna (Chemical and Process Engineering)
The key feature of thermosensitive polymers is the reversible transition between the hydrophilic and hydrophopic forms depending on the temperature. Although the main research efforts are focused on their application in different kinds of drug delivery systems, this phenomenon also allows one to precisely control the stability of solid-liquid dispersions. In this paper research on the application of poly(N-isopropylacrylamide) copolymers in processing of minerals is presented. In the experiments tailings from flotation plant of one of the coal mines of Jastrzębska Spółka Węglowa S.A. (Poland) were used. A laser particle sizer Fritsch Analysette 22 was used in order to determine the Particle Size Distribution (PSD). It was proved that there are some substantial issues associated with the application of thermosensitive polymers in industrial practice which may exclude them from the common application. High salinity of suspension altered the value of Lower Critical Solution Temperature (LCST). Moreover, the co-polymers used in research proved to be efficient flocculating agents without any temperature rise. Finally, the dosage needed to achieve steric stabilization of suspension was greatly beyond economic justification.